Maximizing Income Through Capital, Raw Materials, Labor and Production - Abdul Gani; Zulia Rifda Daulay (International Journal of Science, Technology & Management, 2021)
The purpose of this study was to analyze the effect of capital, raw materials, labor and production on business income for the Batu Bara songket cloth during the Covid-19 pandemic. The data analysis model used is multiple linear regression analysis. The population and sample of 65 craftsmen of Batu Bara songket cloth were used as research samples. Data collection techniques using a questionnaire (questionnaire) with a Likert scale. For data processing using the SPSS Version 22 application. The results showed that all variables of capital, raw materials, labor and production had a positive and significant impact on the business income of Batu Bara songket cloth. The variable that has the greatest influence in increasing business income for the Batu Bara songket cloth is labor.